2022
DOI: 10.3390/bios12090736
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticle-Based Electrochemical Sensing Platform Using Ferrocene-Labelled Peptide Nucleic Acid for the Early Diagnosis of Colorectal Cancer

Abstract: Diagnostic biomarkers based on epigenetic changes such as DNA methylation are promising tools for early cancer diagnosis. However, there are significant difficulties in directly and specifically detecting methylated DNA regions. Here, we report an electrochemical sensing system based on magnetic nanoparticles that enable a quantitative and selective analysis of the methylated septin9 (mSEPT9) gene, which is considered a diagnostic marker in early stage colorectal cancer (CRC). Methylation levels of SEPT9 in CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Advances in the synthesis and engineering of MNPs offer more specific alternatives for diagnosis and treatment of various cancer types [ 19 , 35 ]. The synthesis method plays an essential role in preparation of MNPs with tailored features, suitable for biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in the synthesis and engineering of MNPs offer more specific alternatives for diagnosis and treatment of various cancer types [ 19 , 35 ]. The synthesis method plays an essential role in preparation of MNPs with tailored features, suitable for biomedical applications.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, significant research results have been reported regarding the application of Fe 3 O 4 and/or γ-Fe 2 O 3 in NSCLC targeted therapy [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. To date, it is certain that these studies show both promising results regarding the use of MNPs for lung cancer diagnostic [ 19 ] and also their valuable features as nanocarriers for anticancer drug delivery to the lungs [ 20 ]; however, they are not yet accepted as an efficient clinical approach for humans. The studies reported above describe the use of MNPs obtained by chemical or physical methods.…”
Section: Introductionmentioning
confidence: 99%
“…MNPs offer amplification potential comparable to that of exceptional enzyme labels in electrochemical biosensors, while also providing several advantages, including eliminating the need for timed signal recording and mitigating the risk of denaturation during storage ( Cai et al, 2002 ). Simgle ( Hanoglu et al, 2022 ) developed an MNPs-based electrochemical biosensor for assessing the methylation septin9 (mSEPT9) gene in early-stage colorectal cancer (CRC) ( Figure 8 ). This biosensor leverages the stability and signal amplification capabilities of MNPs to accurately and selectively detect methylated SEPT9 gene sequences which serve as a diagnostic marker for CRC.…”
Section: Application Of Mnps-based Biosensor For Poctmentioning
confidence: 99%
“…This alternative was carried out by Povedano et al in 2018, who developed two different electrochemical affinity biosensing approaches for 5-mC in DNA that do not require bisulfite or PCR testing [ 78 ]. Likewise, more recently, Hanoglu et al reported an electrochemical sensing system based on MNPs that enabled quantification of the methylated septin-9 gene, which is considered a biomarker in early CRC [ 79 ].…”
Section: Antibody-loaded Nanosystems For Crc Diagnosismentioning
confidence: 99%